Multiple founder effects are followed by range expansion and admixture during the invasion process of the raccoon (Procyon lotor) in Europe. Issue 4 (31st January 2017) - Fischer, Marietta L.; Salgado, Iván; Beninde, Joscha; Klein, Roland; Frantz, Alain C.; Heddergott, Mike; Cullingham, Catherine I.; Kyle, Christopher J.; Hochkirch, Axel
Abstract: Aim: Understanding colonization dynamics is crucial for management of invasive species. We compare the genetic structure of historical (Central Europe) and recent (Spain) invasive populations with native and captive populations of the North American raccoon ( Procyon lotor ). Our aim was to analyse the effects of colonization age on genetic population structure, understand the role of captive individuals as potential founders and test the role of rivers for the dispersal of the species. Location: North America, Spain, Central Europe. Methods: We genotyped wild‐caught raccoons from Spain and Central Europe ( N  =   596), zoos ( N  =   57) and the native range ( N  =   153) at 16 microsatellite loci and sequenced a mitochondrial DNA fragment (Control Region). We analysed population genetic structuring with Bayesian assignment methods and a FCA. In a landscape genetic analysis, we tested the effect of waterways in the dispersal of the species. Results: We detected 16 genetic clusters (inbaps ), supporting the hypothesis of multiple introductions and ongoing releases in the invasive range. The native population showed nearly no genetic structure, the Central European clusters showed signals of admixture, whereas the Spanish clusters were clearly separated. Admixture of the Central European clusters was probably caused by recent contact of populations with different origin. The landscape genetic analysis showed that rivers represent neither barriers nor corridors in Central Europe. Main conclusions: As the Spanish populations are genetically more diverse than the Central European, we expect increased within‐population diversity when the still isolated populations merge after range expansion. As our results provide evidence for gene flow between zoos and free‐ranging populations, better control of pet trade is essential in the management efforts concerning this invasive species. Our study shows that genetic analyses can help to reconstruct invasion processes, which is important for better understanding and effective management of invasive species.